City Production through Sexuality and Space Appropriationas Perspective: A Case Study at Sao Pauloas Gay Street (Global Journal of Human-Social Science, 2013)
Which identities a space can acquire? What about a public space? For instance, a street, how can it be defined and who is able to do so? A street can acquire a "sexual identity"? This article concentrates on some aspects observed in my master"s dissertation. My research was ethnographic based and captures the appropriation of public spaces in large cities as a way of defining a socio-sexual identity, in this case,FreiCaneca Street in Sao Paulo. In this article, I will address some of the data from my participant observation, which tells how the identity"s definitions are constructed at street"s space and at the spaces on the street. I also tackle how these settings interact with everyday local basis, make possible the separation into groups and trigger political demonstrations. Moreover, I address how these definitions help to outline the city of São Paulo and shift their centralities.
Keywords: urban sociology; ethnographic research; sexualities; urban planning; sE3; o paulo city